Sensor system design for respiratory sound analysis - Yu, Tian (2019)
When we breathe, our lungs and airways produce a variety of different sounds. When a person is suffering from respiratory diseases, the sounds produced, such as wheezes and crackles can be used by doctors to help in the diagnosis of the patient. Thus, if the sounds are detected early, diagnosis and treatment of respiratory illnesses such as asthma and chronic lung diseases can begin as soon as possible. [1] With certain types of respiratory illnesses, it is beneficial for the patient to be able to constantly monitor their breathing. However, current monitoring needs to be done by doctors with specialized equipment and training, making constant monitoring impossible. With a portable respiratory device, the goal of constant monitoring can be achieved. The portable respiratory device consists of a microphone in an acoustic housing in order to amplify respiratory sounds. The microphone is then connected to any device capable of inserting a 3.5mm microphone jack, in this case a mobile phone and the resulting input signals were ran through Matlab, whereby a signal graph for it is generated. The acoustic housings were designed and 3D printed using stainless steel in varying shapes and dimensions to explore and compare the effect of amplification. A total of 3 shapes were produced, cylindrical, conical and parabolic with variations in the diameter and height of each of the shapes. Tests were done with a range of monotone signals with frequencies ranging from 20Hz to 16oooHz, with particular emphasis on the frequency range of 176Hz to 4000Hz. The cylindrical housing had the best amplification results for the lower frequency range and the parabolic housing had the best amplification results for the higher frequency range. A second set of tests were also done with two additional cylindrical housings, c3 and c5, with their diameter and height reduced to half the original value respectively. Of these two housings, reducing the diameter showed slight to somewhat significant improvements in the amplification magnitude while reducing the height only showed very marginal improvements. In conclusion, the acoustic housings play a crucial role in amplifying sound in order for the portable respiratory device to function. This project provided very valuable results as well as limitations on the device which could be utilized for future acoustic devices both in and out of the biomedical field.